Energy threshold sensitivity for frame loss - Shah, Asadullah; Shah, Zoya (IIUM Press, 2011)
The energy of speech frames can be one of the ways to express least significant frames. The energy is a frame of speech is a time domain measure, speech frames having lowver energy are correlated with low perception as well. In this chapter the 100vest sensitivity energy frames is detailed and that can be utilised for STDM intelligent architectures